2015
DOI: 10.1007/s12570-015-0314-2
|View full text |Cite
|
Sign up to set email alerts
|

New technique in reconstructing humeral head defect in locked posterior dislocation of the shoulder: a case series of nine patients

Abstract: Locked posterior dislocation of the shoulder is uncommon and frequently missed injury. It accounts for 2-4 % of all shoulder dislocations. It is commonly associated with osseous defects in humeral head articular surface known as reverse Hill-Sachs lesion. Numerous surgical procedures are invented to repair this defect with variable outcomes, but evidence-based management strategies are lacking. Among these procedures are as follows: transfer of lesser tuberosity or subscapularis tendon, rotational osteotomy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… Study Outcome Findings Castagna, 2009 6 MRI to evaluate subscapularis tendon and humeral head necrosis No evidence of humeral head necrosis, or detachment or fatty infiltration of the subscapularis muscle in any patient at final follow-up Kokkalis, 2013 21 X-ray to evaluate incorporation of morselized allograft into humeral head defect Complete incorporation of morselized allograft into the humeral head defect in all patients at final follow-up Banerjee, 2013 4 X-ray to evaluate glenohumeral osteoarthritis (Samilson-Prieto) and incorporation of lesser tuberosity Complete integration of the lesser tuberosity into the defect in all patients at final follow-up. No signs of osteoarthritis according to Samilson and Prieto Abdel-Hameed, 2015 1 X-ray to evaluate incorporation of lesser tuberosity Complete integration of the lesser tuberosity into the defect in all patients at an average of 8 weeks Shams, 2016 28 X-ray/CT to evaluate incorporation of lesser tuberosity Complete integration of the lesser tuberosity into the defect in all patients within 8-12 weeks Khira and Salama, 2017 19 CT to evaluate incorporation of lesser tuberosity Complete integration of the lesser tuberosity into the defect in all patients at an average of 12 weeks (range, 10-16) Cohen, 2022 9 X-ray to evaluate glenohumeral osteoarthritis (Samilson-Prieto) Grade 1: 6 patients Grade 2: 2 patients Grade 3: 2 patients CT , computed tomography; MRI , magnetic resonance imaging. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Study Outcome Findings Castagna, 2009 6 MRI to evaluate subscapularis tendon and humeral head necrosis No evidence of humeral head necrosis, or detachment or fatty infiltration of the subscapularis muscle in any patient at final follow-up Kokkalis, 2013 21 X-ray to evaluate incorporation of morselized allograft into humeral head defect Complete incorporation of morselized allograft into the humeral head defect in all patients at final follow-up Banerjee, 2013 4 X-ray to evaluate glenohumeral osteoarthritis (Samilson-Prieto) and incorporation of lesser tuberosity Complete integration of the lesser tuberosity into the defect in all patients at final follow-up. No signs of osteoarthritis according to Samilson and Prieto Abdel-Hameed, 2015 1 X-ray to evaluate incorporation of lesser tuberosity Complete integration of the lesser tuberosity into the defect in all patients at an average of 8 weeks Shams, 2016 28 X-ray/CT to evaluate incorporation of lesser tuberosity Complete integration of the lesser tuberosity into the defect in all patients within 8-12 weeks Khira and Salama, 2017 19 CT to evaluate incorporation of lesser tuberosity Complete integration of the lesser tuberosity into the defect in all patients at an average of 12 weeks (range, 10-16) Cohen, 2022 9 X-ray to evaluate glenohumeral osteoarthritis (Samilson-Prieto) Grade 1: 6 patients Grade 2: 2 patients Grade 3: 2 patients CT , computed tomography; MRI , magnetic resonance imaging. …”
Section: Resultsmentioning
confidence: 99%
“…Nine studies with a total of 97 shoulders (96 patients) met the criteria for inclusion. 1 , 3 , 4 , 6 , 9 , 19 , 21 , 24 , 28 All studies were uncontrolled case series published between 2009 and 2022, with five (56%) being published since 2016. Six studies were retrospective in nature, while three were prospective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior shoulder dislocations are associated in 30 to 90% of cases [ 8 ] with an osteochondral impression fracture of the anteromedial part of the humeral head called a reverse Hill-Sachs lesion (RHSL) [ 9 ]; however, the term posterior shoulder fracture- dislocation is usually only used in cases (about one third [ 10 ]) with fractures of the humeral neck or the tuberosities [ 11 ]. Alternatively, Robinson et al [ 12 ] have suggested referring to the latter as "complex" fracture-dislocations, as opposed to "simple" fracture-dislocations involving only an impression fracture (RHSL).…”
Section: Introductionmentioning
confidence: 99%